The Impact of Sex and Gender on the Multidisciplinary Management of Care for Persons With Parkinson's Disease - Göttgens, Irene; van Halteren, Angelika D.; de Vries, Nienke M.; Meinders, Marjan J.; Ben-Shlomo, Yoav; Bloem, Bastiaan R.; Darweesh, Sirwan K. L.; Oertelt-Prigione, Sabine (Frontiers in Neurology, 2020)
The impact of sex and gender on disease incidence, progression, and provision of care has gained increasing attention in many areas of medicine. Biological factors–sex–and sociocultural and behavioral factors–gender–greatly impact on health and disease. While sex can modulate disease progression and response to therapy, gender can influence patient-provider communication, non-pharmacological disease management, and need for assistance. Sex and gender issues are especially relevant in chronic progressive diseases, such as Parkinson's disease (PD), because affected patients require multidisciplinary care for prolonged periods of time. In this perspective paper, we draw from evidence in the field of PD and various other areas of medicine to address how sex and gender could impact PD care provision. We highlight examples for which differences have been reported and formulate research topics and considerations on how to optimize the multidisciplinary care of persons with PD.